Position of the Latin American Society of Nutrition (SLAN) on the management of conflict of interest - Simón Barquera; Claudia Gabriela García-Chávez; Deborah Navarro-Rosenblatt; Ricardo Uauy; Rafael Pérez-Escamilla; Reynaldo Martorell; Manuel Ramírez-Zea; Karina Sánchez-Bazán (Instituto Nacional de Salud Pública, 2018)
There is solid evidence documenting relationships between the food and beverage industry and academia that show that industry sponsored research is likely to bias results in favor of industry. In Latin America, examples of these situations have been documented in Mexico, Brazil, Chile, Peru, Colombia, and Ecuador , among others. Due to the urgent need for studying and managing relationships between the food and beverage industry and the field of health and nutrition research, in 2017, the President of the Latin American Society of Nutrition (SLAN) appointed a Conflict of Interest Committee (CCI). The CCI was charged with the development of a proposal of a position for the management of conflict of interest (COI) for consideration by SLAN. This document details the work of CCI, and the position adopted by SLAN.